Use of Eculizumab in Pediatric Patients With Transplant Associated Thrombotic Microangiopathy - Gomez-Ganda, Laura; Benitez-Carabante, Maria Isabel; Fernandez-Polo, Aurora; Muñoz-Lopez, Marina; Renedo-Miro, Berta; Ariceta, Gema; Diaz De Heredia, Cristina (Frontiers in Pediatrics, 2021)
Background. Transplant-associated thrombotic microangiopathy (TA-TMA) is a serious complication of hematopoietic stem cell transplantation (HSCT) associated with high morbidity and mortality. High-risk TA-TMA (hrTA-TMA) is characterized by multifactorial endothelial damage caused by environmental stressors, dysregulation of the complement system, and genetic predisposition. Complement inhibitors have significantly decreased mortality and are the current treatment of choice. In this article, we describe our experience with the use of eculizumab in pediatric patients diagnosed with hrT-TMA after HSCT. Method. Retrospective study of pediatric patients with hrTA-TMA treated with eculizumab between January 2016 and December 2020. Results. Four pediatric patients aged 1, 12, 14, and 17 years at the time of HSCT were diagnosed with hrTA-TMA and treated with eculizumab during the study. At diagnosis, they all had renal impairment with proteinuria, and hypertension under treatment with at least two antihypertensive drugs. The patient who presented multisystemic involvement died instead of treatment. The three patients with exclusive renal involvement achieved TA-TMA resolution after treatment with eculizumab for 65, 52, and 40.6 weeks and were able to stop treatment. The two patients with follow-up data one year after eculizumab withdrawal sustained a favorable response. Eculizumab was well tolerated, and with adequate vaccination and antibiotic prophylaxis, did not increase the risk of infection. Conclusions. Eculizumab appears to be both safe and effective for the treatment of hrTA-TMA in patients with renal impairment. Early diagnosis and initiation of treatment may improve response. Eculizumab withdrawal can be contemplated in patients who achieve laboratory and clinical resolution of TA-TMA.